Automatic Fish Feeder Integrated With Solar Photovoltaic For Nutrient Film Technique Aquaponic System - Ahmad Shukeri, Muhamad Waliuddin; Mohammad Radzi, Nur Hanis (Evolution in Electrical and Electronic Engineering, 2023)
Aquaponic is the process of raising aquatic plants and animals in a recirculating system. The phrase aquaponics comes from the word hydroponics, which refers to the cultivation of plants in water, and aquaculture, which is the practice of raising fish in a closed environment (the growing of plants usually in a soil-less environment). The Aquaponics system is a choice a lot today because it has several benefits such as a controlled environment. In an aquaponics system, the fish must still be manually fed in accordance with their feeding schedule and the precise amount of food needed for the entire population. Next, if the food provided does not contain a sufficient amount for the fish, it can lead to stunted growth in both the fish and the accompanying plants. Furthermore, any conventional energy that is created and used will have some form of environmental impact. The purpose of this project is to design an Automatic Fish Feeder integrated with the solar PV system. The system of Automatic Fish Feeder is to give automatically food to the fish at a specific time according to the command that has been given. This is where the Real Time Clock (RTC) function gives the real-time system to operate the 12V DC motor to rotate the drill to push the food into the fish pool at 9.00 a.m. and 6.00 p.m. Overall, the automated fish feeder using solar PV technology is an achievable and environmentally beneficial option for fish farming businesses. It improves feeding precision, decreases labour needs, and helps to make the aquaculture sector more sustainable. Future research might look at additional developments in the design and optimization of this integrated system in order to maximize its benefits and encourage wider usage in the aquaculture sector.